Road cycling and mountain biking produces adaptations on the spine and hamstring extensibility - Muyor, J. M.; Zabala, M. (International Journal of Sports Medicine, 2016)
The purposes of this study were as follows: 1) to analyse the influence of training in road cycling or cross-country mountain biking on sagittal spinal curvatures, pelvic tilt and trunk inclination in cyclists of both cycling modalities; 2) to evaluate the specific spinal posture and pelvic tilt adopted on the road bicycle and cross-country mountain bike; and 3) to compare the spinal sagittal capacity of flexion and pelvic tilt mobility as well as hamstring muscle extensibility among road cyclists, cross-country mountain bikers and non-cyclists. Thirty matched road cyclists, 30 mountain bikers and 30 non-cyclists participated in this study. The road cyclists showed significantly greater thoracic kyphosis and trunk inclination than did the mountain bikers and non-cyclists in a standing posture. On the bicycle, the road bicycling posture was characterised by greater lumbar flexion and more significant anterior pelvic tilt and trunk inclination compared with the mountain biking posture. The thoracic spine was more flexed in mountain biking than in road cycling. Road cyclists had significantly greater hamstring muscle extensibility in the active knee extension test, and showed greater anterior pelvic tilt and trunk inclination capacity in the sit-and-reach test, compared with mountain bikers and non-cyclists.